IMPACT OF CIGARETTE SMOKING AND ALCOHOL INTAKE ON MALE INFERTILITY - ARUL AMUTHA ELIZABETH; KALAISELVI V S; PRABHU K; PRASHANTH KRISHNA; PRASANA VENKATESH E; KAVIMANI .M (International Journal of Pharma and Bio Sciences, 2013)
Chronic alcohol consumption and cigarette smoking adversely affect male reproductive health. This work highlights the influence of both on the sperm quality of infertile male partners. This prospective study was conducted on semen samples of alcoholics- (Group1), smokers-(Group2), habit of both-(Group-3), controls-(Group4). Samples were analysed following WHO guidelines including the percentage of teratoszoospermia, asthenozoospermia , oligospermia and their combination. F-test was done between alcoholics, smokers, and both smokers and alcoholics with controls using SPSS. Teratozoospermia and asthenozoospermia dominated in Group1 whereas asthenozoospermia and oligospermia dominated in Group2. Oligospermia dominated in group 3 and as the age advances all the three variables dominated in group2 and 3. Alcohol intake affects sperm morphology and motility, whereas smoking affects sperm concentration and motility. Progressive deterioration in semen quality is related to increasing quantity of cigarette smoking than alcohol intake.